KONTEKSTUALISASI NILAI-NILAI AKIDAH DAN AKHLAK DALAM NOVEL DIARY UNGU RUMAYSHA KARYA NISAUL KAMILAH TERHADAP MATERI AKIDAH AKHLAK MADRASAH ALIYAH - Kamalia, Durratun Nafiisah; Hidayah, Fathi (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Contextualization is a relevant and meaningful word when be combine with other words without having to change the meaning of the word. In this research, contextualization is used to describe the relationship or relevance between the context of stories in novels and texts, namely textbooks for Pendidikan Akidah Akhlak. The Diary Ungu Rumaysha novel’s as a context source became the first data source in this research. The second data source is textbooks on Pendidikan Akidah Akhlak for class X Madrasah Aliyah as a source of comparison text. This library research using content analysis techniques to find a description of the values ​​of aqidah and moral education (akhlak) contained in the novel. This technique is also used to contextualize the novel with the material. The results of this research indicate that the values ​​of aqidah education in the form of basic values ​​of faith are in harmony with the moral aqidah materials in the chapter of faith in Allah, Angels, the book of Allah, Prophets and Apostles, the last day, qodho 'and qodar. While the moral values ​​include helping, being humble, respecting parents and teachers, having harmony with the material about the commendable morals, husnuzzan, tawwaddu', tasamuh, and ta'awun, the chapter on getting used to the commendable morals of endeavor, tawakkal, patience, gratitude, and qana' ah, and the glory chapter is devoted to parents and teachers.